Biaya dan Penerimaan Usahatani Bawang Merah (Allium cepa L.) Serta Kontribusinya dalam Usahatani Keluarga Petani di Banjarbaru - Muhammad Nor Riandi; Dolok Saribu; Fardianah Mukhyar (AGRIDES: Jurnal Agribisnis Perdesaan, 2015)
Since the last decade, the increased onion demandforraw consumption and seed has not been fulfilled by local production . Thus, the import tents to increase year by year. On the other hand, Indonesia has large arable land which can be used for onion cultivation . Banjarbaru is second largest of onion producers in Kalimantan in 2014. The study calculates the costs and revenues of onion farming and their contribution to the total cost and total revenue of farmer household in Banjarbaru . The RCR (Revenue Cost Ratio) is calculated and the problems faced by farmers also identified.On average, the onion farming generates revenue ID 82.99 million per hectare, while the average total cost is IDR 56.68million per hectare. The cultiv ation is feasible as RCR value is 1.46. Problems faced by farmers are disease exposure (fusarium wilt) andchanging seasons during the planting period.